Molecular Characterization of Spontaneous Mesenchymal Stem Cell Transformation - Rubio, Daniel; Garcia, Silvia; Paz, Maria F.; De la Cueva, Teresa; Lopez-Fernandez, Luis A.; Lloyd, Alison C.; Garcia-Castro, Javier; Bernad, Antonio (PLOS ONE, 2008)
BackgroundWe previously reported the in vitro spontaneous transformation of human mesenchymal stem cells (MSC) generating a population with tumorigenic potential, that we termed transformed mesenchymal cells (TMC).Methodology/Principal FindingsHere we have characterized the molecular changes associated with TMC generation. Using microarrays techniques we identified a set of altered pathways and a greater number of downregulated than upregulated genes during MSC transformation, in part due to the expression of many untranslated RNAs in MSC. Microarray results were validated by qRT-PCR and protein detection.Conclusions/SignificanceIn our model, the transformation process takes place through two sequential steps; first MSC bypass senescence by upregulating c-myc and repressing p16 levels. The cells then bypass cell crisis with acquisition of telomerase activity, Ink4a/Arf locus deletion and Rb hyperphosphorylation. Other transformation-associated changes include modulation of mitochondrial metabolism, DNA damage-repair proteins and cell cycle regulators. In this work we have characterized the molecular mechanisms implicated in TMC generation and we propose a two-stage model by which a human MSC becomes a tumor cell.